(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article presents an analysis of the possibility of optimizing the process of informatics training of future physical education teachers based on taking into account the features of the personality structure, the social order of the information society, the humanitarian potential of science, and the specifics of the relevant field of knowledge in the system of sciences. The psychological and pedagogical features of the process of studying the disciplines of the IT training cycle of future physical education teachers are outlined. The concept of person-oriented learning of informatics disciplines is characterized, which is based on the paradigm of person-oriented education and includes personal, activity and competence approaches.